Education for fall prevention in older adults living in long-term care facilities - Dantas , Eveline Emília de Barros; Muñoz, Rilva Lopes de Sousa (Seven Editora, 2024)
Falls are an important cause of functional decline and morbidity and mortality in the elderly and their incidence is higher with advancing age and in institutionalized patients. Preventive measures are essential to avoid accidents caused by falls, and health education can make a significant contribution to prevention. This chapter discusses the importance of health education aimed at preventing falls in elderly people living in long-term care institutions (LTCIEs).  These institutions are environments where the prevention of falls takes on great importance due to the vulnerability of the residents. Effective strategies in these places include periodically assessing the risk of falls, adapting the environment to make it safer and promoting physical activities to strengthen muscles and balance. Health education plays a crucial role in preventing falls in the elderly, both for health professionals and for the elderly themselves and their caregivers. Training health professionals to systematically assess the risk of falls and implement preventive measures is fundamental. In addition, promoting awareness among the elderly about the risks of falls and providing practical guidelines for prevention is essential to reduce the impact of these events on health and quality of life. DOI:https://doi.org/10.56238/sevened2024.007-041